Faktor-Faktor Yang Mempengaruhi Audit Report Lag Pada Perusahaan Yang Tergabung Di Jakarta Islamic Index - Amin, Syaiful; , Dr. Zulfikar, SE, M.Si (2017)
This research aims to analyze the influence of the opinion of the auditor, the company's size, profitability, size public accountant (KAP), debt to total asset (DTA), audit committee size, and liquidity on the audit report lag. The population of this research is a public company incorporated in the Jakarta Islamic Index (JII) 2013-2015 period. The number of samples number of 15 companies with the method of purposive sampling. The analysis of the data used is multiple linear regression. Research results indicate that the variable size of the public accountant, debt to total asset (DTA), and the liquidity effect on audit report lag, whereas the variable opinions an auditor, the company's size, profitability, and the audit committee size have no effect against the audit report lag. Keywords: auditor's Opinion, company size, profitability, the size of the public accountant, debt to total assets, audit committee size,liquidity, audit report lag.